2015
DOI: 10.1007/s10495-015-1136-y
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis in mammalian oocytes: a review

Abstract: Apoptosis causes elimination of more than 99% of germ cells from cohort of ovary through follicular atresia. Less than 1% of germ cells, which are culminated in oocytes further undergo apoptosis during last phases of oogenesis and depletes ovarian reserve in most of the mammalian species including human. There are several players that induce apoptosis directly or indirectly in oocytes at various stages of meiotic cell cycle. Premature removal of encircling granulosa cells from immature oocytes, reduced levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
185
0
7

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 192 publications
(196 citation statements)
references
References 72 publications
4
185
0
7
Order By: Relevance
“…3C,D). Many factors, including ROS, have been reported to induce oocyte apoptosis (Tiwari et al, 2015). Indeed, increased ROS levels were observed in Kat8…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…3C,D). Many factors, including ROS, have been reported to induce oocyte apoptosis (Tiwari et al, 2015). Indeed, increased ROS levels were observed in Kat8…”
Section: Discussionmentioning
confidence: 98%
“…Several factors can induce oocyte apoptosis in mammals, such as increased levels of reactive oxygen species (ROS) or destruction of oocyte-granulosa cell communication (Tiwari et al, 2015). However, how anti-apoptotic genes are regulated in response to these apoptosis inducers is still not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…12.2). It is believed that apoptosis is the major mechanism involved in the loss of oocytes during cyst breakdown and primordial follicle assembly (reviewed by Tiwari et al 2015). Xu et al (2011) showed that proliferating cell nuclear antigen Fig.…”
Section: Assembly Of Primordial Folliclesmentioning
confidence: 99%
“…That is, during oogenesis, not all meiotic defects drive cells to undergo apoptosis, making oocytes more susceptible to completing meiosis carrying chromosome defects [10]. When apoptosis does occur, both intrinsic and extrinsic pathways are involved in the death of the oocytes at various stages of meiotic prophase [11]. In contrast, spermatocytes with meiotic defects usually undergo apoptosis during pachynema, the transition of prophase I to metaphase I, and/or metaphase I [12].…”
Section: Introductionmentioning
confidence: 99%